Metode Bermain: Upaya Menstimulusi Perkembangan Matematika Anak Usia Dini - Handayani, Fitri Febri; Munawaroh, Faridatul; Kurniawan, Nova Adi; Devianti, Rika (STAI Auliaurrasyidin Tembilahan, 2022)
Mathematics is still considered one of the difficult and frightening subjects to learn. The play method is considered to be able to make the mathematics learning process more enjoyable, so that it can stimulate children's mathematical abilities. The purpose of this study was to determine the mathematical development of Group B children of PAUD Kasih Ibu. This research is a Classroom Action Research (PTK) in collaboration with class teachers. The subjects in this study were as many as 14 children. Data were collected using child ability test sheets, observations, field notes, and documentation. Data analyzed using P= . The results showed that children's mathematical ability in pre-cycle was 42%, cycle I was 72.3% and Cycle II was 99.1%. In addition, children have also been seen 1) like to play, 2) like new things, and 3) children are easily bored, so they need a variety of media and learning methods.